Disposable photonics for cost-effective clinical bioassays: application to COVID-19 antibody testing. Issue 15 (23rd June 2021) - Cognetti, John S.; Steiner, Daniel J.; Abedin, Minhaz; Bryan, Michael R.; Shanahan, Conor; Tokranova, Natalya; Young, Ethan; Klose, Alanna M.; Zavriyev, Alexander; Judy, Nicholas; Piorek, Brian; Meinhart, Carl; et al.
Abstract : Rice-sized (1 × 4 mm) silicon nitride ring resonator photonic sensor chips paired with plastic micropillar fluidic cards for sample handling and optical detection yield a "disposable photonics" assay platform. Abstract : Decades of research have shown that biosensors using photonic circuits fabricated using CMOS processes can be highly sensitive, selective, and quantitative. Unfortunately, the cost of these sensors combined with the complexity of sample handling systems has limited the use of such sensors in clinical diagnostics. We present a new "disposable photonics" sensor platform in which rice-sized (1 × 4 mm) silicon nitride ring resonator sensor chips are paired with plastic micropillar fluidic cards for sample handling and optical detection. We demonstrate the utility of the platform in the context of detecting human antibodies to SARS-CoV-2, both in convalescent COVID-19 patients and for subjects undergoing vaccination. Given its ability to provide quantitative data on human samples in a simple, low-cost single-use format, we anticipate that this platform will find broad utility in clinical diagnostics for a broad range of assays.